When old meets young? Germany's population ageing and the current account - Matthias Schön; Nikolai Stähler (Deutsche Bundesbank, 2019)
In a three-region New Keynesian life-cycle model calibrated to Germany, the Euro area (without Germany) and the rest of the world, we analyze the impact of population ageing on net foreign asset and current account developments. Using unsynchronized demographic trends by taking those of Germany as given and assuming constant population everywhere else, we are able to generate German current account surpluses of up to 15% of GDP during the first half of this century. However, projected demographic trends from 2000 to 2080 in OECD countries (and China in an additional analysis) are much more synchronized. Feeding these into our model suggests that the average annual German current account surplus from 2000 to 2018 that should be attributed to ageing reduces to around 2.83% (1.23%) of GDP, with a maximum at 4.3% (2.7%) in 2006 (when taking into account China), turning negative around 2035.
Keywords: E43; E44; E52; E58; 330; Population Ageing; Net Foreign Assets; Global Imbalances; DSGE Models